CREDENCE: A silver lining in the dark cloud of diabetic nephropathy - Hanai, Ko; Babazono, Tetsuya (Journal of diabetes investigation, 2020)
[...]SGLT2 inhibitors have a strong effect in reducing the risk of deteriorating heart failure, which is closely associated with advanced diabetic nephropathy. A recent study of patients with heart failure and a reduced ejection fraction showed that the risk of deteriorating heart failure or death from cardiovascular causes was lower in the dapagliflozin group than in the placebo group, regardless of the presence of diabetes . [...]the kidney‐protective effects observed in the CREDENCE study might have been noted because of the interruption of the vicious circle involving diabetic nephropathy and heart failure . [...]the CREDENCE study has provided evidence that canagliflozin administration is a beneficial therapy that delays kidney disease progression in patients with advanced diabetic nephropathy.